True or False?
For any three real numbers ( x , y , z ) , ∣ x ∣ + ∣ y ∣ + ∣ z ∣ ≤ ∣ x − y + z ∣ + ∣ x + y − z ∣ + ∣ − x + y + z ∣ .
Notation:
∣
⋅
∣
denotes the
absolute value function
.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Letting
x y z = a + b = b + c = c + a
then the following inequality is clear:
∣ a + b ∣ + ∣ b + c ∣ + ∣ c + a ∣ ≤ 2 ∣ a ∣ + 2 ∣ b ∣ + 2 ∣ c ∣
How do we know that the first substitution is possible?
Log in to reply
Hm, good question. What wouldn't make it possible?
Log in to reply
It is on the solution writer to justify that the substitution is possible. One way of doing so is to make it explicit like what Aron did. It is not on the reader/critiquer to justify that "this is definitely not possible".
Note: It is possible to come up with substitutions that do not work (for various reasons). This is more commonly an issue in functional equations and inequalities. As an explicit example, if we additionally required that a, b, c were positive (say in order to apply AM-GM), then such values do not exist for x = 1 , y = 2 , z = 5 .
Problem Loading...
Note Loading...
Set Loading...
Note that
2 x − y + z + 2 x + y − z 2 − x + y + z + 2 x + y − z 2 x − y + z + 2 − x + y + z = x = y = z
Since ∣ a ∣ + ∣ b ∣ ≥ ∣ a + b ∣ ,
2 ∣ x − y + z ∣ + 2 ∣ x + y − z ∣ 2 ∣ − x + y + z ∣ + 2 ∣ x + y − z ∣ 2 ∣ x − y + z ∣ + 2 ∣ − x + y + z ∣ ≥ ∣ x ∣ ≥ ∣ y ∣ ≥ ∣ z ∣
By adding the inequations, we get ∣ x ∣ + ∣ y ∣ + ∣ z ∣ ≤ ∣ x − y + z ∣ + ∣ x + y − z ∣ + ∣ − x + y + z ∣